Bimbingan Rohani Untuk Menurunkan Kenalakan Ramaja - Santi Nurul Putri M; Aji Satrio K; Ike Yuliani; Sheva Bayu F; Faiarudin Aulia W (Pusat Riset dan Inovasi Nasional, 2023)
This research explores the effectiveness of spiritual guidance, especially the Islamic approach, in dealing with juvenile delinquency. The adolescent phase, as an important transition period, tends to be marked by significant physical and mental changes. Uncontrolled juvenile delinquency can be detrimental to individuals and society. Research emphasizes the application of spiritual guidance to early adolescents and pre-adolescents to prevent deviant behavior. Spiritual guidance, as a process of providing direction and advice with religious values, has a crucial role in forming positive character. Findings from previous research show that spiritual guidance, including Islamic counseling, vent sessions, and religious activities, is effective in reducing levels of juvenile delinquency. Teenagers who receive spiritual guidance tend to have a positive mindset, use their time well, and have a better religious understanding. Although the study makes important contributions, resource limitations, methodological variations in previous studies, and the lack of long-term studies need to be addressed. Therefore, future research must overcome these limitations to provide deeper insight into the role of spiritual guidance in dealing with juvenile delinquency.